2013
DOI: 10.4049/jimmunol.1202058
|View full text |Cite
|
Sign up to set email alerts
|

G Protein–Coupled Receptor Kinase 6 Deficiency Promotes Angiogenesis, Tumor Progression, and Metastasis

Abstract: G protein coupled receptor kinases (GRKs) phosphorylate the activated form of G protein coupled receptors (GPCRs) leading to receptor desensitization and down-regulation. We have recently shown that the chemokine receptor, CXCR2, couples to GRK6 to regulate cellular responses including chemotaxis, angiogenesis and wound healing. In this study, we investigate the role of GRK6 in tumorigenesis using murine models of human lung cancer. Mice deficient in GRK6 (GRK6−/−) exhibited a significant increase in Lewis lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…In epithelial cells, a functional screening identified GRK6 as a critical mediator in integrin-mediated cell adhesion and migration of tumor cells [35], and GRK6 deficiency reportedly promotes CXCR2 receptor-mediated tumor progression and metastasis in a lung carcinoma model [36]. It would be interesting to investigate whether the modulation of cell migration by these GRKs is mostly related to their canonical role as specific or more active regulators of given GPCRs in different cell types or novel substrates and interactors as those identified for GRK2 are also targeted.…”
Section: Role Of Grks Other Than Grk2 In Cell Migrationmentioning
confidence: 99%
“…In epithelial cells, a functional screening identified GRK6 as a critical mediator in integrin-mediated cell adhesion and migration of tumor cells [35], and GRK6 deficiency reportedly promotes CXCR2 receptor-mediated tumor progression and metastasis in a lung carcinoma model [36]. It would be interesting to investigate whether the modulation of cell migration by these GRKs is mostly related to their canonical role as specific or more active regulators of given GPCRs in different cell types or novel substrates and interactors as those identified for GRK2 are also targeted.…”
Section: Role Of Grks Other Than Grk2 In Cell Migrationmentioning
confidence: 99%
“…GRK6 is the most recently identified member of the family of GRKs (10). Recent studies demonstrated that the overexpression of GRK6 exerts an important role in the process of transduction of pain signals (11,(28)(29)(30)(31). Previous studies also revealed that endogenous GRK6 molecules contribute to the desensitization of M3 muscarinic acetylcholine in the human SH-SY5Y neuroblastoma cell line (32).…”
Section: Discussionmentioning
confidence: 95%
“…levels in CRC. Previous studies have revealed that GRK6 expression contributes to the progression of several types of cancer (11,16,18,(28)(29)(30)(31). Despite these diverse studies, the precise functions and the mechanistic actions of GRK6 have not been defined completely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations